2015
DOI: 10.1111/apa.13251
|View full text |Cite
|
Sign up to set email alerts
|

Children who were treated with oral immunotherapy for cows' milk allergy showed long‐term desensitisation seven years later

Abstract: Oral immunotherapy was an effective and safe way of desensitising schoolchildren with persistent CMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
2
24
0
3
Order By: Relevance
“…The recommended treatment for food allergies is allergy avoidance, but milk oral immunotherapy (OIT) has shown promise in promoting desensitization to cow's milk protein in children with persistent CMA . Long‐term outcomes of milk OIT have been published in small studies, with success rates varying from 31% to 65% . More long‐term follow‐up studies on OIT are needed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommended treatment for food allergies is allergy avoidance, but milk oral immunotherapy (OIT) has shown promise in promoting desensitization to cow's milk protein in children with persistent CMA . Long‐term outcomes of milk OIT have been published in small studies, with success rates varying from 31% to 65% . More long‐term follow‐up studies on OIT are needed …”
Section: Introductionmentioning
confidence: 99%
“…This study was based on previous milk OIT studies conducted in Finland . By gathering real‐life results from previous clinical studies, we were able to monitor the effects of milk OIT in 296 patients over 11 years.…”
Section: Introductionmentioning
confidence: 99%
“…After achieving maintenance dose of OIT, many patients are asked to continue an equivalent amount of the food allergen in their diet. Follow-up studies on children who underwent OIT in a previous trial showed that these children continued to tolerate a food equivalent in their diet safely [7,8].…”
Section: Oral Immunotherapymentioning
confidence: 99%
“…In the initial study, authors reported that 24 of the 28 children were consuming milk daily at 36 months from initiation of OIT. Of the 24 participants responding to a questionnaire 7 years after initiation of milk OIT, 8 (33%) had discontinued milk altogether, 2 consumed limited amounts, and 14 (58%) reported daily consumption of milk, with 3 among these reporting symptoms associated with milk ingestion [68] . The mixed results of these follow-up studies point to the necessity of further study to improve the safety and efficacy of OIT.…”
Section: Long-term Follow-upmentioning
confidence: 99%